Spectrum of clinical and biochemical profile and its importance in diabetic ketoacidosis: a tertiary care hospital experience in Gujarat - Jansari, Trupti R.; Chauhan, Amit P.; Patel, Jigna P.; Jasani, Jasmin H. (International Journal of Research in Medical Sciences, 2023)
Background: Diabetes mellitus (DM) is a disorder of multiple etiologies, and diabetic ketoacidosis (DKA) is one of the life-threatening complications of DM. This study was aimed to study the clinical and biochemical profile of DKA patients. Methods: We conducted this retrospective study at a tertiary care hospital in Gujarat. We included total 100 patients above the age of 18 years having DM, presented with DKA. A detailed history, clinical examination and biochemical tests were carried out: random blood sugar, urinalysis, arterial blood gas analysis, serum ketone, HbA1c, serum creatinine, serum electrolytes- potassium and sodium and serum osmolality. The results were analysed using Microsoft excel. Results: Out of total 100 patients, 76 (76%) patients had type 1 DM and 24 (24%) had type 2 DM, 42 (42%) were in the age group of 18-30 years. The mean age was 39.75±12.14 years. There were 56 (56%) males and 44 (44%) females with male: female ratio of 1.3:1. Most common clinical features of DKA were nausea/vomiting (88%), breathlessness (43%) and fever (35%). The main biochemical parameters altered were blood sugar (>400 mg/dl in 41%) and serum ketones (≥5 in 84%) as well as majority of patients (64%) had their HbA1c level between 11-15% with the mean HbA1c value of 12.25±2.43%. Conclusions: DKA is a frequently observed emergency with high mortality rate. Education regarding symptoms of ketoacidosis, not missing insulin doses especially during illness, strict adherence to treatment and lifestyle modifications can greatly reduce DKA occurrence.